Implications of the human microbiome in inflammatory bowel diseases - Bakhtiar, Syeda M. (2013)
The study of the human microbiome or community of microbes and collection of genomes found in the human body is one of the fastest growing research areas because many diseases are reported to be associated with microbiome imbalance or dysbiosis. With the improvement in novel sequencing techniques, researchers are now generating millions of sequences of different sites from the human body and evaluating specific differences in microbial communities. The importance of microbiome constituency is so relevant that several consortialike MetaHIT and HMP are focusing mainly on the human microbiome. The aim of this review is to highlight points of research in this field, mainly focusing on particular factors that modulate the microbiome and important insights into its potential impact on our health and well-being.